Differential Motion Analysis of the Planar 3-RRR Fully Compliant Parallel Mechanism - Li Yaqiong; An Ziming; Zhu Dachang; Zhou Lei (Jixie chuandong)
By establishing apseudo-rigid-body model of the planar 3-RRR type fully compliant parallel mechanism,and using micro approximation algorithm,the displacement jacobian matrix between the input and output is got,the displacement vector differential mapping relation between input and output under the micro motion case is researched,and the numerical validation is carried out,the simulation of it is conducted with ANSYS software,the theoretical reference basis for differential motion analysis of this kind of planar parallel mechanism and spatial parallel mechanism with multiple input and multiple output characteristics is provided.